2020
DOI: 10.7554/elife.58046
|View full text |Cite
|
Sign up to set email alerts
|

Formin-like 1 mediates effector T cell trafficking to inflammatory sites to enable T cell-mediated autoimmunity

Abstract: Lymphocyte migration is essential for the function of the adaptive immune system, and regulation of T cell entry into tissues is an effective therapy in autoimmune diseases. Little is known about the specific role of cytoskeletal effectors that mediate mechanical forces and morphological changes essential for migration in complex environments. We developed a new Formin-like-1 (FMNL1) knock-out mouse model and determined that the cytoskeletal effector FMNL1 is selectively required for effector T cell traffickin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 56 publications
4
29
0
Order By: Relevance
“…In vitro models suggest that the requirement for FMNL1 is dependent on the restrictiveness of the barrier to be crossed, with FMNL1 deficiency only impairing T cell migration through narrow pores or constrictions, such as those found in non-lymphoid tissue endothelial barriers. This is consistent with in vitro TEM experiments where FMNL1 was only important for the diapedesis step of TEM [110].…”
Section: Extravasationsupporting
confidence: 90%
See 1 more Smart Citation
“…In vitro models suggest that the requirement for FMNL1 is dependent on the restrictiveness of the barrier to be crossed, with FMNL1 deficiency only impairing T cell migration through narrow pores or constrictions, such as those found in non-lymphoid tissue endothelial barriers. This is consistent with in vitro TEM experiments where FMNL1 was only important for the diapedesis step of TEM [110].…”
Section: Extravasationsupporting
confidence: 90%
“…Compared to the other cytoskeletal effectors, FMNL1 appears unique in that it seems specifically involved in the trafficking of activated T cells and only to non-lymphoid tissues [110]. In vitro models suggest that the requirement for FMNL1 is dependent on the restrictiveness of the barrier to be crossed, with FMNL1 deficiency only impairing T cell migration through narrow pores or constrictions, such as those found in non-lymphoid tissue endothelial barriers.…”
Section: Extravasationmentioning
confidence: 99%
“…Studies in mDIA1 KO mice have revealed the role of mDIA1 in promoting T cell emigration from the thymus and recruitment into peripheral tissues ( Vicente-Manzanares et al, 2003 ; Eisenmann et al, 2007 ; Sakata et al, 2007 ). More recently, FMNL1 has been shown to mediate effector T cell trafficking to inflammatory sites in the context of T cell-mediated autoimmunity, by promoting actin polymerization at the back of the nucleus to help T cells overcome restrictive barriers ( Thompson et al, 2020 ). In the context of the T cell IS both mDIA1 and FMNL1 contribute to the reorientation of the MTOC and their deletion in CD8 + T cells reduces cytotoxic activity ( Gomez et al, 2007 ).…”
Section: Molecular Control Of Actin Remodeling At the Immunological Synapse Via The Prism Of Actin-related Pidsmentioning
confidence: 99%
“…In transmigration experiments, CD4+ T cells from ERU horses showed increased migration rates, which was linked to increased expression of the protein formin-like 1 (FMNL1) in the membranes of these cells ( 33 ). As shown in a new FMNL1 knock-out mouse model, FMNL1 deficiency impedes extravasation and trafficking of T cells to sites of inflammation ( 35 ), further undermining the importance of this protein and its functional effects in ERU pathogenesis. Furthermore, lymphocytes from ERU horses displayed significantly higher cell motility, cell speed and directness toward selected chemoattractants, especially IFNγ, and toward the ERU autoantigen CRALBP, in live-cell imaging experiments ( 36 ), which was associated to lower abundance of the protein septin 7 in these cells ( 32 , 36 ).…”
Section: Peripherymentioning
confidence: 99%